Development of micrologistics system of delivery of finished products of metallurgical enterprises by rail transport - Турпак, Сергій Миколайович; Грицай, Сергій Васильович; Острогляд, Олена Олександрівна (Eastern-European Journal of Enterprise Technologies, 2014)
Logistics flows of metallurgical enterprises have certain characteristics, conditioned by their capacity and dependence on complex technological processes. Enterprises have reliable levers of influence mostly on in-plant transport processes, therefore, the studies to improve optimization methods of transport-storehouse processes in this element of logistics chain were performed. Micrologistics systems of interaction of flow processes for basic general options of deliveries were developed, the structure of which is as follows: the flow of cargo, rolling stock, information, documents and payments is shown in the time field. Operations that are performed with the corresponding flows are marked on the ordinate axis. The proposed system is a tool to identify “bottlenecks” in the field of graph of explicitly presented processes and optimize the supply chain as a whole with minimum total costs. In fact, the research results are improved methods to develop transportation flow charts. It was proposed to optimize the system of delivery of finished products of metallurgical enterprise by in-plant transport based on logistics principles. In the improved system, the overall cargo delivery term is reduced mostly by eliminating some operations with the rolling stock. Some cargo operations and execution of documents are no longer needed. A methodology for evaluating the effectiveness of change of transport-technological process of delivery of finished products was proposed.